A worldwide charter for all children with asthma. Issue 5 (6th March 2020) - Szefler, Stanley J.; Fitzgerald, Dominic A.; Adachi, Yuichi; Doull, Iolo J.; Fischer, Gilberto B.; Fletcher, Monica; Hong, Jianguo; García‐Marcos, Luis; Pedersen, Søren; Østrem, Anders; Sly, Peter D.; Williams, Siân; et al.
Abstract: Childhood asthma is a huge global health burden. The spectrum of disease, diagnosis, and management vary depending on where children live in the world and how their community can care for them. Global improvement in diagnosis and management has been unsatisfactory, despite ever more evidence‐based guidelines. Guidelines alone are insufficient and need supplementing by government support, changes in policy, access to diagnosis and effective therapy for all children, with research to improve implementation. We propose a worldwide charter for all children with asthma, a roadmap to better education and training which can be adapted for local use. It includes access to effective basic asthma medications. It is not about new expensive medications and biologics as much can be achieved without these. If implemented carefully, the overall cost of care is likely to fall and the global future health and life chance of children with asthma will greatly improve. The key to success will be community involvement together with the local and national development of asthma champions. We call on governments, institutions, and healthcare services to support its implementation.